RESEARCH OF INFLUENCING OF THE CAPILLARY RAISING OF UNDERGROUND WATERS ON DISTRIBUTION OF OIL CONTAMINATION IN SOILS - Скиба, Е. Е. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The theory of capillary phenomena formation is considered in clay, loam, sandy loam and sand. It has been determined height and capillary rise rate of underground water differs and grows with increase of soils dispersion. The data of capillary rise of water in soils has been simulated and the effect upon oil pollution spread has been investigated. It has been proved capillary forces hold oil area in soils at the certain height of the soil flux.